2022
DOI: 10.7150/ijbs.68724
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the critical role of the PXR in preventing carcinogenesis and chemotherapeutic drug resistance

Abstract: Pregnane x receptor (PXR) as a nuclear receptor is well-established in drug metabolism, however, it has pleiotropic functions in regulating inflammatory responses, glucose metabolism, and protects normal cells against carcinogenesis. Most studies focus on its transcriptional regulation, however, PXR can regulate gene expression at the translational level. Emerging evidences have shown that PXR has a broad protein-protein interaction network, by which is implicated in the cross signaling pathways. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 160 publications
(232 reference statements)
0
13
0
Order By: Relevance
“…It has been reported that PXR can be modified by acetylation, phosphorylation, ubiquitination, and SUMOylation through protein-protein interactions (Figure 2A), indicating that PXR is implicated in posttranslational modifications which may ultimately affect its transcriptional regulation and metabolic detoxification process. The interaction centered by PXR will illustrated the multifunctional property of it in different signaling pathways (41). Being part of a chaperone protein complex consisting of heat shock protein 90 (Hsp90) and CAR cytoplasmic retention protein (CCRP), PXR is predominantly localized in the cytoplasm (42).…”
Section: The Transcriptional Regulatory Characteristics Of Pxrmentioning
confidence: 99%
“…It has been reported that PXR can be modified by acetylation, phosphorylation, ubiquitination, and SUMOylation through protein-protein interactions (Figure 2A), indicating that PXR is implicated in posttranslational modifications which may ultimately affect its transcriptional regulation and metabolic detoxification process. The interaction centered by PXR will illustrated the multifunctional property of it in different signaling pathways (41). Being part of a chaperone protein complex consisting of heat shock protein 90 (Hsp90) and CAR cytoplasmic retention protein (CCRP), PXR is predominantly localized in the cytoplasm (42).…”
Section: The Transcriptional Regulatory Characteristics Of Pxrmentioning
confidence: 99%
“…Inhibition of PXR may be an important adjuvant therapy to increase radiosensitization in cancers, taking advantage of PXR-ATF3-ATM signaling pathway. Our data provide a rationale for clinical development of PXR antagonists for treating IR resistant to anticancer therapies that depend on promoting DNA damage response and repair ( 44 ). PXR antagonists ketoconazole, fucoxanthin (FUC), and SPA70 were reviewed in reference ( 44 ).…”
Section: Discussionmentioning
confidence: 97%
“…Our data provide a rationale for clinical development of PXR antagonists for treating IR resistant to anticancer therapies that depend on promoting DNA damage response and repair ( 44 ). PXR antagonists ketoconazole, fucoxanthin (FUC), and SPA70 were reviewed in reference ( 44 ). Pharmaceutical inhibition of PXR-ATF3-ATM pathway by PXR antagonists will sensitize cells to DNA damage and dampen the cell survival in a cancer cell that was treated with IR.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, ABCB1 genotyping prior to the initiation of everolimus therapy is not recommended [ 6 ], consistent with the findings of our current study. Because the activation of PXR induces the expression of drug-metabolizing enzymes, such as CYP3A and ABC transporters (e.g., P-glycoprotein) [ 13 , 14 , 26 ], differences in PXR activation may influence interindividual variability in everolimus pharmacokinetics because everolimus is a substrate of both CYP3A and P-glycoprotein. In the univariate analysis, the dose-adjusted C 0 and AUC 0-12 values of everolimus in patients with the NR1I2 8055C/C genotype were significantly lower than those in patients with other genotypes; however, no changes in the elimination half-life were observed among genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The three most common single nucleotide polymorphisms (SNPs) identified in the ABCB1 transporter are 1236C>T, 2677G>T/A, and 3435C>T [ 12 ]; however, in a previous study using a population pharmacokinetic model of 53 renal transplant recipients, ABCB1 1236C>T, 2677G>T/A, and 3435C>T polymorphisms did not affect the apparent oral clearance of everolimus [ 9 ]. P-glycoprotein and CYP3A is regulated by activated pregnane X-receptor (PXR, NR1I2 ), an important nuclear receptor [ 13 , 14 ], and the 7635G>A (rs6785049) and 8055C>T (rs2276706) polymorphisms in the NR1I2 gene for human PXR are associated with altered CYP3A4 regulation [ 15 ]. However, in this previous study using a pharmacokinetic model [ 9 ], NR1I2 7635G>A and 8055C>T also did not affect the apparent oral clearance of everolimus.…”
Section: Introductionmentioning
confidence: 99%